GAYA KOMUNIKASI PIMPINAN DALAM MEMOTIVASI SEMANGAT BEKERJA DI SUB BAGIAN KOMUNIKASI PIMPINAN PEMKAB TEGAL - Imanidar, Oka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
Communication has a very important role to support all activities, especially within the organization. When there is no communication between leaders and employees or vice versa, it will hinder the process of performance of organizational goals. The leader's communication style must also be in accordance with the situation and conditions of the organization he leads. Because it can affect the performance and productivity of its employees. The purpose of this study was to describe the communication style of the leadership of the Tegal Regency Leadership Communications Sub Division in motivating the work spirit of the employees. This study uses descriptive qualitative research with data collection techniques by observation, interviews and documentation. There are 6 informants selected by the researcher. Results Based on research on leadership communication style in motivation to work in the Tegal Regency Leadership Communications Sub-Section, it can be concluded that the leadership in the Leadership Communications Sub-Section uses communication. In motivation, the leader provides instructions, instructions, information and explanations to employees. However, it is not uncommon for leaders here to use horizontal communication, namely exchanging messages or ideas with each member in the organization. This is in an open attitude that is owned by the leadership. Leadership communication style Sub Division of Leadership Communications uses two communication styles, namely The Equalitarian Style and The Relinguishing Style. In the motivation to work employees, the leadership of the Sub-Division of Leadership Communications uses two-way communication. This is very effective in influencing employees to work hard. Because two-way communication is very important used by leaders to create good and effective communication.